Analysis of School-Based Management (MBS) On School Health Business Activities (UKS) In Utara Sumedang District - Aprilia, Renita; Muhtar, Tatang; Alif, Muhammad Nur; Lengkana, Anggi Setia (UNIVERSITAS NEGERI MAKASSAR, 2025)
Enhancing student health and improving the quality of education are the core objectives of the School Health Program (UKS). However, its implementation continues to face several challenges, including inadequate facilities, limited student awareness of health, and low parental engagement. This study aims to evaluate the application of School-Based Management (MBS) in supporting the effectiveness of the UKS program. A qualitative approach with a phenomenological design was used. Data were gathered through interviews, observations, and document analysis, involving school principals, physical education teachers (PJOK), and students as participants. Data analysis was conducted using NVivo 12 software to explore relationships among variables. The findings reveal that the implementation of SBM within the UKS program has yet to be fully optimized. Schools struggle to provide adequate health facilities, develop student health cadres, and coordinate with community health centres (Puskesmas). Limited human resources and a lack of parental involvement also remain significant barriers. In addition, UKS policies in some schools are not yet systematically structured, leading to less effective implementation. Nevertheless, the UKS program holds strong potential to enhance the quality of health education. Ensuring greater effectiveness and sustainability requires more focused policies, adequate resource support, and strengthened collaboration with external health professionals.